2017
DOI: 10.1007/s40336-017-0235-x
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid intraoperative imaging techniques in radioguided surgery: present clinical applications and future outlook

Abstract: PurposeThis review aims to summarise the hybrid modality radioguidance techniques currently in clinical use and development, and to discuss possible future avenues of research. Due to the novelty of these approaches, evidence of their clinical relevance does not yet exist. The purpose of this review is to inform nuclear medicine practitioners of current cutting edge research in radioguided surgery which may enter standard clinical practice within the next 5–10 years. Hybrid imaging is of growing importance to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 99 publications
1
30
0
2
Order By: Relevance
“…To provide the surgeon with the best guidance as currently possible, many recent advances focus on the use of optical and nuclear detection modalities within a single surgical workflow [153,208,209]. Within the field of image-guided surgery, fluorescence imaging is rapidly gaining popularity, often providing detailed real-time visualization of targeted tissues within their anatomical context [210].…”
Section: Optical Emissionsfluorescencementioning
confidence: 99%
See 2 more Smart Citations
“…To provide the surgeon with the best guidance as currently possible, many recent advances focus on the use of optical and nuclear detection modalities within a single surgical workflow [153,208,209]. Within the field of image-guided surgery, fluorescence imaging is rapidly gaining popularity, often providing detailed real-time visualization of targeted tissues within their anatomical context [210].…”
Section: Optical Emissionsfluorescencementioning
confidence: 99%
“…Furthermore, ex vivo analysis of surgical specimens within the OR has also been suggested for direct margin evaluation [224]. Although no research is reported on this format yet, one could imagine a hybrid application where γ rays are used for lesion localization and Cerenkov imaging is used for margin evaluation [208].…”
Section: Background and Recent Advances Cerenkov Radia-mentioning
confidence: 99%
See 1 more Smart Citation
“…Hybrid intraoperative imaging solutions coupling the functional information provided by the radionuclides with anatomical details obtained with optical techniques, such as NIR fluorescence‐radio‐guided surgery, are currently under investigation to augment surgical precision …”
Section: New Intraoperative Imaging Technologies Overviewmentioning
confidence: 99%
“…Medipix2 photon counting readout chip. This imaging probealso adopted in an experimental CT/SPECT system dedicated to the breast [34], and for imaging at nuclear facilities [27,28] could be adopted for various tasks as preoperative or intraoperative SLN localization with 99m Tc radiotracer in breast cancer or melanoma patients [18,[35][36][37][38], breast imaging with 99m Tc-Sestamibi [39], thyroid imaging [40], breast RGS with 125 I and/or 99m Tc radiotracers [41], and in hybrid imaging systems [42]. The same detector unitdeveloped within the Medipix2 Fig.…”
Section: Introductionmentioning
confidence: 99%